FROM SPECTACLES TO LASER; A PARADIGM SHIFT - Aamir Ali Choudhry (Journal of University Medical & Dental College, 2020)
The use of glass to magnify image was reported by an Arabian scientist,ibn al-Haytham. He mentioned this in his book, written in 11th century. The name of his book was Alhazen’s book of optics. After hundred years this book was translated from Arabic to Latin. It took another hundered year to invent spectacles. This step of invention is attributed to an unknown Italian scientist. But that unknown Italian scientist kept this art to himself and sold glasses and did not share it with his colleagues.